Blackmail - Campbell, Rick (Navy Commander) (St. Martin's Press, 2017)
"The U.S. aircraft carrier patrolling the Western Pacific Ocean is severely damaged by a surprise salvo of cruise missiles. While the Russian government officially apologizes, claiming it was the result of fire control accident during a training exercise, it was instead a calculated provocation. With the U.S. Pacific fleet already severely under strength, the Russian President decides that the US response is a clear indication of their weakness, militarily and politically, and initiates a bold plan. Political unrest is spreading through the Eastern European states. The Russian Northern Fleet moves swiftly in the Mediterranean Sea, the Russian army is moving west to the border, and Russian Baltic and Black Sea Fleets are mobilized. In one bold strike, the Russian army moves to reoccupy a large number of the industrialized areas of the former USSR, while blockading the vital sea passages through which the world's oil and natural gas transit. To make matters worse, Russia's Special Forces have wired every major oil and natural gas pipeline with explosives. If the U.S. makes one move to thwart Russia, they'll destroy them all. The U.S. is risking disaster if it acts, but the alternative is quite possibly worse. Torn between the unthinkable and the impossible, the only possible move--to launch an attack on all fronts, simultaneously"--